Sugar Price Stabilization in Malaysia : Assessment of the Conflicts and Resolutions Towards Food Security - Ambrose, Angelina Fatimah (2012)
The Malaysian government’s intervention of sugar price stabilization policy following international sugar price volatility has come under great scrutiny, with arguments to allow for market forces to correct it. However, the domestic economy incurs efficiency losses that call for some degree of market intervention to stabilize domestic sugar price. The significance of the study lies therein that it will shed light on the extent and nature of sugar price stabilization in the Malaysian economy. Despite reservations on the overall desirability of price stabilization mechanism and it remains unclear in terms of its usefulness to all commodity items. What should become evident is the extent to which government intervention of sugar price stabilization policy coupled with sugar long term contract has successfully protected the local economy against extreme volatile world sugar prices. Therefore reform efforts should be well based on logic, taking into account the facts and complexity of the sugar market. Public awareness has been insulated from the reality of the sugar problem. The challenge of defending the right course of policy action will continue if perceptions about the value of sugar cannot be established clearly. Acknowledging aspects of the changing values of sugar internationally affects the Malaysian economy and is hoped to set us on a more safe and sane course for the future.